Effects of keratinocyte growth factor on skin epithelial differentiation of human amnion epithelial cells - Fatimah, SS; Tan, GC; Chua, K; Tan, AE; Azurah, AGN; Hayati, AR (Elsevier Sci Ltd, 2024)
The aim of the present study was to determine the effects of KGF on the differentiation of cultured human amnion epithelial cells (HAECs) towards skin keratinocyte. HAECs at passage 1 were cultured in medium HAM's F12: Dulbecco's Modified Eagles Medium (1:1) supplemented with different concentrations of KGF (0, 5, 10, 20,30 and 50 ng/ml KGF). Dose-response of KGF on HAECs was determined by morphological assessment; growth kinetic evaluation; immunocytochemical analysis; stemness and epithelial gene expression quantification with two step real time RT-PCR. KGF promotes the proliferation of HAECs with maximal effect observed at 10 ng/ml KGF. However, KGF decreased the sternness genes expression: Oct-3/4, Sox-2, Nanog3, Rex-1, FGF-4, FZD-9 and BST-1. KGF also down-regulates epithelial genes expression CK3, CK18; CK19, Integrin-beta 1, p63 and involucrin in cultured HAECs. No significant difference on the gene expression was detected for each Nestin, ABCG-2, CK1 and CK14 in KGF-treated HAECs. Immunocytochemical analysis for both control and KGF-treated HAECs demonstrated positive staining against CK14 and CK18 but negative staining against involucrin. The results suggested that KGF stimulates an early differentiation of HAECs towards epidermal cells. Differentiation of KGF-treated HAECs to corneal lineage is unfavourable. Therefore, further studies are needed to elucidate the roles of KGF in the differentiation of HAECs towards skin keratinocytes. (C) 2012 Elsevier Ltd and ISBI. All rights reserved.